1998
DOI: 10.1007/bf01280319
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical localization of cellulase activity in pollen mother cells of david lily during meiotic prophase I and its relation to secondary formation of plasmodesmata

Abstract: Summary. Cellulase activity was localized at the ultrastructural level in pollen mother cells (PMCs) of David lily [Lilium davidii var. willmottiae (Wilson) Roffill] at different stages of meiotic prophase I. The enzyme was observed to appear at the early leptotene stage and reached its highest level at the subsequent zygotene stage, and its subcellular distribution revealed by the presence of electron-dense deposits of reaction product was found to be restricted exclusively to the endoplasmic reticulum (ER), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Recently, ultrastructurally cytochemical investigations revealed that the CC was formed via local wall digestion by cellulase released by endoplasmic reticulum (ER)-derived vesicles (WANG et al 1998). However, we still lack the detailed ultrastructural features characterizing this process, especially those at the early stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, ultrastructurally cytochemical investigations revealed that the CC was formed via local wall digestion by cellulase released by endoplasmic reticulum (ER)-derived vesicles (WANG et al 1998). However, we still lack the detailed ultrastructural features characterizing this process, especially those at the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…However, these early views were not supported by experimental evidence. Most recently, in exploring the mechanism responsible for secondary PD formation in lily PMCs, we found that the reaction product of cellulase was restricted to the ER, ER-derived vesicles and the wall (especially at the sites of secondary PD and CC under formation) (WANG et al 1998). This finding suggested that the wall digesting enzymes were synthesized in rough ER and then secreted directly, via smooth ER and ER-derived vesicles, into the CW by exocytosis, where they brought about a local wall breakdown, leading to the formation of both secondary PD and CC.…”
Section: Biogenesis Of Ccs In Pmcs Of Lilymentioning
confidence: 99%
“…3b, channel 3) and, on the other, de novo (Fig. 3b, channel 2) on the cell wall regions lacking any plasmodesmata (Wang et al 1998;Yu et al 2004;Mursalimov et al 2010).…”
Section: Cellular Mechanismsmentioning
confidence: 95%
“…Their emergence in the cell wall allows the nuclei and other organelles to migrate from one cell to another. Unlike plasmodesmata, CCs have no internal structure, such as desmotubules and, as a rule, CCs are considerably larger than plasmodesmata; the CC diameter ranges from 50 to 3,500 nm (Heslop-Harrison 1966;Wang et al 1998;Wang et al 2002;Mursalimov et al 2010). In addition, CCs may occupy over 25 % of the cell surface (HeslopHarrison 1966).…”
Section: Cellular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation